Tissue MicroRNA Expression as a Predictor of Response to Immunotherapy in NSCLC Patients - Grenda, Anna; Krawczyk, Paweł; Błach, Justyna; Chmielewska, Izabela; Kubiatowski, Tomasz; Kieszko, Stanisław; Wojas-Krawczyk, Kamila; Kucharczyk, Tomasz; Jarosz, Bożena; Paśnik, Iwona; Borowiec-Bar, Małgorzata; Frąk, Małgorzata; et al. (Frontiers in Oncology, 2021)
Introduction Protein expression of PD-L1 in tumor cells, which is so far the only validated predictive factor for immunotherapy, is regulated by epigenetic and genetic factors. Among the most important ones that regulate gene expression are microRNAs. Materials and Methods The study included 60 patients with NSCLC who underwent 1st or 2nd line immunotherapy with pembrolizumab or nivolumab. FFPE materials were collected before the start of immunotherapy. We examined relative expression of microRNAs (miR-141, miR-200a, miR-200b, miR-200c, miR-429, miR-508-3p, miR-1184, miR-1255a) and mRNA of PD-L1 gene. Copy number variation (CNV) by qPCR and FISH methods were assessed. Two SNPs in promoter region rs822335 and rs822336 of CD274 gene were examined. Expression of PD-L1 protein on tumor cells was assessed by immunohistochemistry (IHC). The response rate to immunotherapy and progression free survival (PFS) measured in weeks and overall survival (OS) measured in months from the start of immunotherapy were evaluated. Results Response to immunotherapy was observed in 9 patients (10%, including one complete response), disease stabilization in 22 patients (36.7%), and progression in 29 patients (48.3%). Significantly higher (p=0.015) expression of miR-200b and significantly lower (p=0.043) expression of miR-429 were observed in responders compared to patients who did not respond to immunotherapy. The PFS median in the whole group of patients was 16 weeks, and the OS median was 10.5 month. The median PFS was significantly higher in patients with high miR-200b expression (HR=0.4253, 95% CI: 0.1737-1.0417, p=0.05) and miR-508 (HR=0.4401, 95% CI: 0.1903-1.0178, p=0.05) and with low expression of miR-429 (HR=0.1288, 95% CI: 0.01727-0.9606, p=0.0456) compared to patients with low and high expression of these molecules, respectively. In patients with high mRNA expression of the PD-L1 gene the median PFS was not significantly higher than in patients with low mRNA expression (HR=0.4965; 95% CI; 0.2013-1.2249; p=0.12) The median OS was higher in patients with low expression of miR-429 (HR=0,6288, 95%CI: 0,3053-1,2949, p=0.06) compared with patients with high expression of this miRNA. Conclusion MicroRNA levels of PD-L1 may be an auxiliary marker in assessing the effectiveness of monoclonal antibody treatment in patients with non-small cell lung cancer.